Prospective Evaluation of Opioid Use After Adoption of a Prescribing Guideline for Outpatient Foot and Ankle Surgery. (November 2019) - Bhashyam, Abhiram R.; Keyser, Cornelia; Miller, Christopher P.; Jacobs, Jennifer; Bluman, Eric; Smith, Jeremy T.; Chiodo, Christopher
Background: In 2016, our provider group adopted an initial prescription opioid maximum guideline to reduce overprescription of opioids. The purpose of this study was to prospectively assess opioid consumption patterns following implementation of this guideline in patients undergoing outpatient foot and ankle surgery. Methods: Over a 1-year period, we prospectively analyzed opioid prescription and use patterns of 303 consecutive patients. Opioid consumption was verified by pill counts completed at the 2- and 6-week postoperative visits. The morphine equivalent dose was calculated for each prescription and converted to the equivalent 5-mg oxycodone "pill." We used the regression coefficients from a regression model of opioid consumption to create a revised guideline for maximum initial opioid prescriptions based on patient age, bony vs nonbony procedure, and anatomic location (forefoot/midfoot/hindfoot/ankle). Results: On average, 37.4 pills were prescribed and 18.9 pills used (47.6% utilization). Only 17.2% of patients used their full prescription quantity. By 2 weeks, 88% of patients no longer used opioids. Only 1.3% of patients used prescription opioids beyond 6 weeks. Independent risk factors for increased opioid consumption were younger age ( P = .003), male sex ( P = .007), recent preoperative opioid use ( P = .019), bony procedures ( P < .001), and ankle/hindfoot procedures ( P = .016 and P < .001). Conclusion: This study showed the amount of opioid consumption for patients undergoing foot and ankle procedures. We present a modified guideline for the maximum initial prescription of opioids following outpatient foot and ankle procedures that can be used as a benchmark for further study in decreasing overprescribing. Level of Evidence: Level II, prospective observational cohort study.